NATURE, NATIONALISM, FAITH: MAGELANG CULTURAL IDENTITY THROUGH STUDENTS’ LOCAL FOLKTALE-BASED CREATIVE WRITING - Puri Bakhtawar; Muhammad Nur Hanif; Desy Fitrianingsih; Catur Wulan Sari (Pujangga, 2026)
The latest Creative Writing learning paradigm highlights the importance of the integration of sociocultural dimensions in the Creative Writing learning process. The integration of sociocultural dimensions can be conducted through the use of local folktales as the base in students’ Creative Writing works. Although previous studies have examined the use of local folktales in Creative Writing, limited attention has been given to how cultural identities are represented through students’ Creative Writing based on local folktales. This study aims to investigate the cultural identity of Magelang as represented in students’ Creative Writing works adapted from Magelang local folktales. This study employed a qualitative research design with qualitative content analysis to investigate the representation of Magelang cultural identity in students’ local folktale-based Creative Writing short stories. Through the analysis of 18 students’ Creative Writing works, the findings of this study reveal three dominant narrative patterns that represent Magelang’s cultural identity, including: narratives of nature, narratives of nationalism, and narratives of faith. Narratives of nature highlight that nature is seen as a sacred site: a source of life in Magelang society’s worldview. Narratives of nationalism show that Magelang is rich with historical values and nationalism as its cultural and societal identity. Narratives of faith show that faith and religion are one of the core values in building Magelang cultural identity. It can be concluded that the students’ Creative Writing serves not only as a literary expression, but also as a medium of preserving and reaffirming Magelang cultural identity.